2021
DOI: 10.2166/washdev.2021.260
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of groundwater quality and human health risk associated with chromium exposure in the industrial area of Ranipet, Tamil Nadu, India

Abstract: Rapid urbanization and industrialization leading to an increase in groundwater contamination is a serious environmental concern in India in recent years. The risk of groundwater contamination is highly pronounced in and around the Ranipet industrial area causing a threat to human health and a balanced ecosystem. In this study, 40 groundwater samples were collected in and around the industrial area of Ranipet which is largely producing Chromium (Cr) and Chromium-based chemicals. The heavy metal contamination an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…The results of total dissolved solids (TDS) are between 132 and 2247 mg/L, with a mean of 344 mg/L (Figure 3c), where the highest concentrations were observed in the MTB2 and MTB3 wells of the locality of Mata Tambor. The results agree with those reported by Vijayakumar et al (2022) [16], who found values between 212 and 1905 mg/L, with a mean of 751.3 mg/L; likewise, Lanjwani et al (2020) [18] found higher concentrations, of 318 to 7411 mg/L. The presence of TDS is due to the elements, minerals, salts, anions, and cations dissolved in the water sample.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results of total dissolved solids (TDS) are between 132 and 2247 mg/L, with a mean of 344 mg/L (Figure 3c), where the highest concentrations were observed in the MTB2 and MTB3 wells of the locality of Mata Tambor. The results agree with those reported by Vijayakumar et al (2022) [16], who found values between 212 and 1905 mg/L, with a mean of 751.3 mg/L; likewise, Lanjwani et al (2020) [18] found higher concentrations, of 318 to 7411 mg/L. The presence of TDS is due to the elements, minerals, salts, anions, and cations dissolved in the water sample.…”
Section: Resultssupporting
confidence: 90%
“…Regarding the EC results, values between 228.152.08 and 45005.033 mS/cm with a mean of 681 mS/cm (Figura 3b) were detected; they were lower than those reported by Vijayakumar et al (2022) [16] who found a mean of 1067.65 mS/cm. The EC of the samples depends on the concentrations of various species of ions and their capacity to transport energy in a solution, which is affected by the presence of metal ions in the water [17].…”
Section: Resultscontrasting
confidence: 55%
“…Groundwater is the water that exists below the ground surface. Groundwater systems are extremely dynamic and it is more compatible with pollution because water is constantly moving downward (Vijayakumar et al 2021;Patel et al 2022). Groundwater sources are our current and future water demand reserves and they differ from other water sources in that they perform a critical function in terms of cleanliness and accessibility that cannot be replaced (Shirazi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…So, groundwater is a globally important and valuable renewable resources of the human life and the economic development of the humans as well as the whole country. In developing countries like India, groundwater contamination has become a serious concern in the post-industrialization era (Vijayakumar et al 2021). Basically, groundwater is a water that exists underground in saturated zones below the land surface.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%